(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Tho article tracos out the evolution of relationship with marketing and discuss Its Importance In today’s highly turbulent marketing environment. The thoughts of various management thinkers on relationship marketing approach have been also incorporated along with an overview on the implementation of Relationship Marketing In the organization. The article envisages relat,onshlp marketing as a recipe for marketing in the organization. The article envisages relationship marketing as a recipe for marketing success.